Evolution Halal Industry and The impact to Global Trade : Analysis Comparative Markets Main - Cita Ayni Putri Silalahi; M. Guffar Harahap; Muhammad Radian syah (INTERNATIONAL, Journal of Sharia Business Management, 2024)
Study This done For know whether evolution halal industry impact on global trade , with do testing on market main halal industry namely Indonesia. Research done with method quantitative with use analysis comparative with technique data processing , namely Statistical Package For The Social Sciences. As for what becomes indicator in study This Export halal products , Halal Certification , Infrastructure And Ecosystem Industry , Growth Market Halal Industry , Attracting Investors, MSMEs, and Institution Halal Certification and test influence before And after halal industry is growing And the impact to global trade . And it was concluded from results study that after develop influential halal industry to proven global trade from results testing conducted​